2019
DOI: 10.1186/s40517-019-0150-7
|View full text |Cite
|
Sign up to set email alerts
|

On the geothermal potential of crustal fault zones: a case study from the Pontgibaud area (French Massif Central, France)

Abstract: Exploring new geothermal targets requires the understanding of the factors affecting fluid circulation and heat transfer (Rowland and Sibson 2004; Fairley 2009). Understanding the distribution of permeability in the crust remains an essential component for the general comprehension of a geothermal model in the crustal domain, and therefore for the success of a geothermal prospect (Moeck 2014). Nowadays in France, most geothermal exploration licences are located in sedimentary basin areas or within graben struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 86 publications
(112 reference statements)
5
35
0
1
Order By: Relevance
“…The second major difference deals with the value of temperature anomalies, which do not exceed 50-60°C in the case of an inclined fault zone, whereas it exceeds 80°C in the vertical case. These results are consistent with the 2D models of Duwiquet et al (2019), who also found higher thermal anomalies for vertical faut zones.…”
Section: Cases With a Depth-dependent Permeabilitysupporting
confidence: 92%
See 4 more Smart Citations
“…The second major difference deals with the value of temperature anomalies, which do not exceed 50-60°C in the case of an inclined fault zone, whereas it exceeds 80°C in the vertical case. These results are consistent with the 2D models of Duwiquet et al (2019), who also found higher thermal anomalies for vertical faut zones.…”
Section: Cases With a Depth-dependent Permeabilitysupporting
confidence: 92%
“…When fault permeability is higher, cold downwellings may be favored within the fault, as in the numerical simulations of the Soultz-sous-Forêts geothermal system where fault width equals 100 m (Guillou-Frottier et al, 2013). In the case of the Pontgibaud crustal fault zone (French Massif Central), Duwiquet et al (2019) reproduced present-day surface heat flow and temperature gradient for a maximum permeability of 1.6 10 -14 m², a value for which a high temperature (150°C) hydrothermal reservoir could settle at a depth of 2.5 km. It may be worth to consider the possibility of a critical fault permeability above which positive thermal anomalies disappear in favor of negative anomalies, but Lopez and Smith (1995) already showed that the role of host rock permeability has also to be taken into account (see also Della-Vedova, 2008).…”
Section: Typical Structural Settings and Permeability Values For Hydrmentioning
confidence: 96%
See 3 more Smart Citations